(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
The novel Aranysárkány (The Golden Kite) by Dezső Kosztolányi serves as the scene to an existential catastrophe brought about by a set of habits, wishes and symbols of a small-town environment: there unfolds a story of the personal, family and professional failure and tragedy of dr. Antal Novák, high-school teacher and thunderstorm-monitor. The study aims to reveal the possible causal relations of this process of collapse, to outline the motivational set, as well as to interpret the motifs; at the same time, it presents the novel as a specific educational and developmental one, portraying the main character Antal Novák as a teacher/educator.